Bräutigam und Braut oder Vater und Tochter?: Literarisches und Dokumentarisches zu 1Kor 7,36-38 - Arzt-Grabner, Peter (Biblische Notizen, 2006)
In contrast to the traditional interpretation of 1Cor. 7:36-38 that the passage concerns the relationship between a father and his daughter, who has been promised to a young man for marriage, contemporary scholars argue that Paul’s focus is on a relationship between bridegroom and bride. The article examines the critical terms and context on the background of documentary papyri and literary texts, that have not been taken into account so far or far enough, and of Graeco-Roman marriage contracts. The results of this study favor the traditional interpretation.